Evaluation of Screening Assays for the Detection of Influenza A Virus Serum Antibodies in Swine. Issue 1 (27th February 2014) - Goodell, C. K.; Prickett, J.; Kittawornrat, A.; Johnson, J.; Zhang, J.; Wang, C.; Zimmerman, J. J.
Summary: Increased surveillance of influenza A virus (IAV) infections in human and swine populations is mandated by public health and animal health concerns. Antibody assays have proven useful in previous surveillance programmes because antibodies provide a record of prior exposure and the technology is inexpensive. The objective of this research was to compare the performance of influenza serum antibody assays using samples collected from pigs (vaccinated or unvaccinated) inoculated with either A/Swine/OH/511445/2007 γ H1N1 virus or A/Swine/Illinois/02907/2009 Cluster IV H3N2 virus and followed for 42 days. Weekly serum samples were tested for anti‐IAV antibodies using homologous and heterologous haemagglutination‐inhibition (HI) assays, commercial swine influenza H1N1 and H3N2 indirect ELISAs, and a commercial influenza nucleoprotein (NP)‐blocking ELISA. The homologous HIs showed 100% diagnostic sensitivity, but largely failed to detect infection with the heterologous virus. With diagnostic sensitivities of 1.4% and 4.9%, respectively, the H1N1 and H3N2 indirect ELISAs were ineffective at detecting IAV antibodies in swine infected with the contemporary influenza viruses used in the study. At a cut‐off of S/N ≤ 0.60, the sensitivity and specificity of the NP‐blocking ELISA were estimated at 95.5% and 99.6%, respectively. Statistically significant factors which affected S/N results include vaccination status, inoculum (virus subtype), day post‐inoculation and the interactions between those factors ( P < 0.0001). Serum antibodies against NP provide an ideal universal diagnostic screening target and could provide a cost‐effective approach for the detection and surveillance of IAV infections in swine populations.